1965
DOI: 10.1161/01.cir.31.3.328
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Fiberoptics in Clinical Cardiac Catheterization

Abstract: Intracardiac blood oxygen saturation was determined in 31 patients, at cardiac catheterization, by means of a fiberoptic in vivo hemoreflection system, giving an immediate report. When compared to in vitro spectrophotometric analysis of samples obtained through a second catheter, a standard error of estimate of only 1.99-per cent saturation (r = 0.966) was found for the higher speed instrument (response time 0.07 second) and 1.13-per cent saturation (r = 0.992) for the slower instrument (response time 1.5 seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 20 publications
(4 reference statements)
0
21
0
Order By: Relevance
“…[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] In the last years, their expansion has been benefiting from the development of telecommunications and OF communications, in particular, which are offering high-quality, miniaturized, and affordable optoelectronic components at competitive prices.…”
Section: 25mentioning
confidence: 99%
See 2 more Smart Citations
“…[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] In the last years, their expansion has been benefiting from the development of telecommunications and OF communications, in particular, which are offering high-quality, miniaturized, and affordable optoelectronic components at competitive prices.…”
Section: 25mentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37][38][39][40][41][42] Their working principle is based on the variation of the light intensity or amplitude. Some possible configurations have been described: 43,44 an OF placed in front of a movable and reflecting mirror (Fig.…”
Section: 25mentioning
confidence: 99%
See 1 more Smart Citation
“…The reflected light has been analyzed spectrophotometrically, on the basis of the linear relationship between the measurand and the ratio of the intensities of the two reflected wavelengths [25]. The following years have been particularly prolific using this or similar techniques in the laboratory and clinical environments [26][27][28][29][30][31][32][33][34][35].…”
Section: Earlier Intensity-modulated Configurationsmentioning
confidence: 99%
“…Polanyi and Hehir (1962) and Enson et al (1962) reported a method to measure oxygen saturation of blood by inserting a fiber optics into a blood vessel, in which a light was projected directly into blood stream via fiber optic light guide and a reflected light was measured. This method has advantages that oxygen saturation can be known in vivo without blood sampling and its rapid change concomitant with respiration or cardiac pulsation can be measured (Enson et al 1964;Gamble et al 1965;Frommer et al 1965;Harrison et al 1966;Mook et al 1968). The principle is based on the phenomenon that the reflected light from red blood cells changes with the change of oxygen saturation of blood as oxygen saturation plays in the absorp tion light for spectrophotometry (Nahas 1951).…”
mentioning
confidence: 99%